Characteristics of Age and Gender Distribution of Abused and Neglected Children - National Strategy and Prevention Measures - Đerić, Danijela; Konstantinović, Strahinja; Milčić, Maša (Medical Word, 2024)
The problem of child abuse and neglect in the world is increasing, there is an increasing number of children with this problem and there is a need to define this problem as well as legal guidelines and guidelines to work more efficiently. Injuries in abused and neglected children are very diverse, rarely endangering the life of the child or leading to permanent disability, and must be hospitalized and surgically treated as emergencies.The retrospective study included 79 patients treated at the Clinic for Pediatric Surgery Orthopaedics and Traumatology (KDHOT), University Clinical Center Niš. The results show that there was no statistically significant distribution by gender. The average age of all hospitalized children in the examined period is 7.97 ± 6.67 years with a median of 7.00 years.In the largest percentage of cases, abusers are peers or relatives. Although the public today more than ever is warned about various cases of violence against children, this is a problem that is solved in practice by a small number of experts and which is not given as much importance as necessary to solve this problem.
Keywords: Child abuse; prevention